2016
DOI: 10.1177/0890117116677798
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leadership Support for Health Promotion in Employee Wellness Program Participation, Perceived Job Stress, and Health Behaviors

Abstract: Results from the study suggest that employees' perceptions of organizational leadership support for health promotion are related to their participation in wellness activities, perceived job stress levels, and health behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 32 publications
0
51
0
4
Order By: Relevance
“…To address individual-level factors, managers in this study adopted various strategies such as flexible "wellness hour, " targeted information dissemination, site visitations, individual coaching and creating opportunities for employees to ask questions during staff meetings. These are laudable strategies as research has shown that employees' engagement in WHP improves when they perceive strong organizational support and involvement (35).…”
Section: Discussionmentioning
confidence: 99%
“…To address individual-level factors, managers in this study adopted various strategies such as flexible "wellness hour, " targeted information dissemination, site visitations, individual coaching and creating opportunities for employees to ask questions during staff meetings. These are laudable strategies as research has shown that employees' engagement in WHP improves when they perceive strong organizational support and involvement (35).…”
Section: Discussionmentioning
confidence: 99%
“…are highly demanding while simultaneously allowing little control. Many areas of work correspond to this model, whereby individuals have high workloads but relatively little autonomy in completing their assigned tasks [21][22][23]. Therefore, high job demands and low job control play a role in perceived psychological distress and, as a consequence, the workers who experience a combination of these 2 domains are considered more exposed to occupational stress [24][25][26][27].…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…1 This presents employers with a unique opportunity to reach a large segment of the population that otherwise may not be exposed to, or engaged in, organized health improvement efforts. Over 30 years of research suggests that comprehensive, well-designed, well-executed, and properly evaluated workplace health promotion (WHP) programs can lead to reductions in healthcare utilization and costs 2,3 ; enhance work performance 4 ; improve employee health and well-being factors 5 such as job stress, 6 sleep, 7 physical activity and nutrition 8 ; impact value-on-investment metrics such as job satisfaction and quality of work 9 ; and, in some cases, may offer positive business results such as bolstering stock market performance 1012 and a positive return-on-investment (ROI). 13–16…”
mentioning
confidence: 99%